THE EFFECT OF PATERNALISTIC LEADERSHIP STYLE, WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE (DEPARTMENT OF EDUCATION OF CENTRAL MAMBERAMO DISTRICT, 2025) - Sem Guani; Hermien Tridayanti; Joko Suyono (Finance : International Journal of Management Finance, 2025)
This study was conducted to examine the Influence of Paternalistic Leadership Style and Work Environment on Employee Performance with Job Satisfaction as an Intervening Variable in the Central Mamberamo Regency Education Office. The population in this study was 40 people using saturated samples. This study used a quantitative approach, the data for this study were obtained through questionnaires filled out by 40 respondents of the Central Mamberamo Education Office employees. The data analysis method used was the Smart PLS SEM method. This study tested four variables, namely: Paternalistic Leadership Style (X1), work environment (X2) as an independent variable, job satisfaction (Z) as a mediating variable and employee performance (Y) as a dependent variable. The results of the study showed that: Paternalistic leadership style did not affect employee performance, work environment and job satisfaction affected employee performance and job satisfaction could mediate paternalistic leadership style and work environment on employee performance. Keywords: Paternalistic Leadership Style, Work Environment, Job Satisfaction and Employee Performance .